Human Resource Management, Healthcare Worker Job Satisfaction, and Quality of Health Services in Hospitals: A Literature Review (Community Engagement and Emergence Journal (CEEJ), 2026)
Background: The quality of healthcare services in hospitals is critically shaped by how human resources are managed. Despite extensive global evidence, empirical studies from public regional hospitals (RSUD) in Indonesia remain scarce, leaving a contextual gap. Job satisfaction of healthcare workers is theorized as a key mediating mechanism between human resource management (HRM) practices and service quality outcomes. Objective: This review synthesizes empirical evidence from Scopus-indexed and other peer-reviewed journals (2020–2025) to map the relationships among HRM practices, healthcare worker job satisfaction, and quality of health services in hospital settings. Methods: A narrative literature review was conducted using Scopus, PubMed, Web of Science, and Google Scholar. Search terms included “human resource management,” “healthcare service quality,” “job satisfaction,” “healthcare workers,” and “hospital.” Articles published between 2020 and 2025, written in English, reporting empirical or systematic evidence from hospital settings were included. Results: Fifteen primary articles met inclusion criteria. Evidence consistently demonstrates that HRM practices (recruitment, training and development, compensation, and performance management) significantly predict healthcare worker job satisfaction. Job satisfaction, in turn, mediates the pathway from HRM to service quality, measured through patient safety, clinical effectiveness, and patient-reported experience. High-performance work systems (HPWS) and HRM bundle approaches showed the strongest associations with quality outcomes. Conclusion: Effective HRM is a foundational lever for healthcare service quality, operating substantially through the mediating role of employee job satisfaction. Future research should test this mediation model empirically in Indonesian public hospital contexts.
Keywords: Human Resource Management; Job Satisfaction; Healthcare Service Quality; Healthcare Workers; Hospital